Object integration requires attention: Visual search for Kanizsa figures in parietal extinction. (November 2016) - Gögler, Nadine; Finke, Kathrin; Keller, Ingo; Müller, Hermann J.; Conci, Markus
Abstract: The contribution of selective attention to object integration is a topic of debate: integration of parts into coherent wholes, such as in Kanizsa figures, is thought to arise either from pre-attentive, automatic coding processes or from higher-order processes involving selective attention. Previous studies have attempted to examine the role of selective attention in object integration either by employing visual search paradigms or by studying patients with unilateral deficits in selective attention. Here, we combined these two approaches to investigate object integration in visual search in a group of five patients with left-sided parietal extinction. Our search paradigm was designed to assess the effect of left- and right-grouped nontargets on detecting a Kanizsa target square. The results revealed comparable reaction time (RT) performance in patients and controls when they were presented with displays consisting of a single to-be-grouped item that had to be classified as target vs. nontarget. However, when display size increased to two items, patients showed an extinction-specific pattern of enhanced RT costs for nontargets that induced a partial shape grouping on the right, i.e., in the attended hemifield (relative to the ungrouped baseline). Together, these findings demonstrate a competitive advantage for right-grouped objects, which in turn indicates that in parietal extinction, attentional competition between objects particularly limits integration processes in the contralesional, i.e., left hemifield. These findings imply a crucial contribution of selective attentional resources to visual object integration. Highlights: We performed a visual search study with Kanizsa figures in extinction patients to assess the role of selective attention in object integration processes. Patients exhibit systematic unilateral search costs in a competitive search condition. The costs are particularly pronounced for nontarget objects with a distracting, partial shape in the right, attended hemifield. Attentional resources are required to integrate parts into coherent wholes.